2015
DOI: 10.1128/jvi.01513-15
|View full text |Cite
|
Sign up to set email alerts
|

Y-Box Binding Protein 1 Stabilizes Hepatitis C Virus NS5A via Phosphorylation-Mediated Interaction with NS5A To Regulate Viral Propagation

Abstract: Replication of hepatitis C virus (HCV) is dependent on virus-encoded proteins and numerous cellular factors. DDX3 is a well-HCV is a positive-stranded RNA virus that contains a 9.6-kb genome consisting of a single open reading frame flanked by 5= and 3= nontranslated regions (NTR). An internal ribosome entry site (IRES) in the 5=NTR directs the translation of a polyprotein, which is processed co-and posttranslationally into 10 or more viral proteins (3, 4). HCV infection is sustained by spatiotemporal interpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 89 publications
(151 reference statements)
0
15
0
Order By: Relevance
“…All these reports implied a direct correlation between HCV and liver steatosis. Given that DDX3 interacts with HCV core and NS5A 16 17 18 34 and is down-regulated by HCV infection ( Fig. 1a ), HCV infection may interfere with the DDX3-augmented transactivation activity of HNF4 on MTP promoter leading to reduced MTP expression by which, at least in part, HCV infection induces liver steatosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All these reports implied a direct correlation between HCV and liver steatosis. Given that DDX3 interacts with HCV core and NS5A 16 17 18 34 and is down-regulated by HCV infection ( Fig. 1a ), HCV infection may interfere with the DDX3-augmented transactivation activity of HNF4 on MTP promoter leading to reduced MTP expression by which, at least in part, HCV infection induces liver steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…While at the later stage of infection, suppression of MTP expression is beneficial for the “storage” of HCV virus particles in lipid droplets for its latency and persistent infection 61 . Interestingly, DDX3 was identified as a cellular cofactor of HCV infection 32 33 34 62 63 64 . From this point of view, it makes sense that HCV hijack DDX3 to regulate MTP promoter to aid its virus propagation and persistent infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore how YB-1 regulates the HCV life cycle, we first examined the interaction between NS5A and YB-1, and our data clearly identify YB-1 as a novel NS5A-interacting protein [23] , and that YB-1 regulates HCV RNA replication. Furthermore, by comparing the effects of knockdown of YB-1, before and after HCV infection, on intracellular HCV RNA levels and the formation of the replication complexes, we presented evidences to indicate that YB-1 is involved in the early stage, but not the steady state, of HCV RNA replication.…”
mentioning
confidence: 99%
“…H. Wu Lee, unpublished data and ref. [27] ), and both factors associate with core, NS3, NS5A and the HCV RNA [4,23,[27][28][29][30] , implying that they function as a complex at least in some steps of the HCV life cycle. However, while DDX3 promotes HCV IRES-mediated translation [31,32] , we found that YB-1 moderately inhibits HCV translation early in the Figure 1.…”
mentioning
confidence: 99%